Isolation of myo-inositol-1-phosphate synthetase from wild type and an inositol-less variant Neurospora crassa - A. Zsindely; M. Szabolcs; J. Ardi; M. Schablik; A. Kiss; G. Szabo (Fungal Genetics Reports, 1977)
Isolation of myo-inositol-1-phosphate synthetase from wild type and an inositol-less variant